Модель доступу до хмарної інфраструктурі та аналіз її імовірнісно-часових характеристик - Педан, М. М. (ХНУРЕ, 2019)
The given work is devoted to the implementation effective model of access to the cloud infrastructure hosted on the data center of the standard architecture, and the assessment its performance indicators based on the analysis probability-time characteristics. In particular, formulas have been obtained for analyzing such quality indicators as the probability of blocking a request and the average delay time in the provision of a cloud service, which will allow to estimate the delay in connecting users to virtual machines. A numerical analysis has been made of the dependence of some the characteristics of the given load and the parameters model of access to cloud infrastructure.